Binding of RHOA G17V to p300 enhances its HAT activity: a new mechanism of epigenetic deregulation in TFH lymphoma - David Vallois; Mélanie Juilland; Kalliopi Ioannidou; François Lemonnier; Edoardo Missiaglia; Bettina Bisig; Margot Thome; Laurence de Leval (Blood Advances)
Abstract: The RHOA G17V mutation is highly recurrent in T follicular helper (TFH) cell lymphoma of the angioimmunoblastic type (AITL; 60%-70% of cases) and frequently associated with mutations in other T-cell receptor signaling genes, including CD28. Here, we sought to elucidate how RHOA and CD28 variants may work in concert to sustain T-cell activation by generating stable Jurkat T-cell lines expressing wild-type (wt) RHOA or RHOA G17V with wt CD28 or CD28 T195P. Concomitant expression of RHOA G17V and CD28 T195P induced significantly higher levels of interleukin-2 (IL-2) production and NFAT nuclear factor of activated T cells (NFAT) and activator protein 1 (AP1) transcriptional activities than either variant alone upon T-cell activation with agonistic anti-CD3 and anti-CD28 antibodies. We identified the histone acetyltransferase p300 as a major interacting partner of RHOA G17V in our model and human primary T cells. p300 inhibition abolished the increased IL-2 secretion induced by CD3/CD28 stimulation in cells expressing RHOA G17V and/or CD28 T195P. Chromatin immunoprecipitations and immunofluorescence staining revealed an increase of p300-specific H3K18ac and H3K27ac marks at the IL-2 promoter and across whole genome, respectively, in cells expressing RHOA G17V. Finally, immunofluorescence staining of tumor samples from 4 patients with AITL carrying RHOA G17V variant and 4 carrying wt RHOA showed that neoplastic TFH cells with RHOA G17V have increased H3K18ac and H3K27ac levels compared with non-neoplastic T cells. Collectively, these findings uncover a new mechanism of action by which RHOA G17V potentiates CD28 T195P-induced NFAT and AP1 transcriptional activities by enhancing p300 histone acetyltransferase activity and expand the notion that epigenetic deregulation contributes to the pathogenesis of TFH lymphomas.